Foliar Iron and Zinc Modulate the Qualitative and Nutritional Status of Sideritis cypria with Diverse Rates of Phosphorus in Hydroponic Cultivation - Neofytou, Giannis; Chrysargyris, Antonios; Xylia, Panayiota; Botsaris, George; Tzortzakis, Nikos G. (My University, 2025)
The increasing demand for medicinal and aromatic plants has expanded their cultivation. Concurrently, the utilization of Sideritis species has also increased, including under-evaluated species such as S. cypria Post. This study evaluated the impact of phosphorus (P: 50, 75, and 100 mg L−1) concentrations in hydroponic nutrient solution (NS), and foliar applications with iron (Fe) and zinc (Zn), to assess S. cypria yield and quality. Although fresh biomass was unaffected, reduced (50 mg L−1) and increased (100 mg L−1) P levels decreased dry matter content (DM). Furthermore, Zn spraying at 50 mg P L−1 increased DM by 10.2% compared to H2O sprayed plants. Increased P with foliar control reduced chlorophylls content by 45.6%, while foliar Zn negated this effect, increasing it by 71.9%. Leaf P accumulation was also reduced (up to 49.8%) under increased P levels, while foliar Fe modulated this response. Foliar applications enriched leaves with Fe and Zn. However, P levels determined the success of Zn biofortification. Intermediate (75 mg L−1) P levels decreased the phenolics content (up to 240%) and flavonoids (up to 190%), exhibiting reduced antioxidant activity and increased lipid peroxidation. In contrast, foliar applications regulated this effect, leading to reduced malondialdehyde (MDA) levels. Increased P levels enhanced the antioxidant capacity of plants, causing a 184% decrease in H2O2 contents under foliar control. Finally, a significant antibacterial activity was presented by the application of intermediate and increased P levels, regardless of foliar applications. Ultimately, the tailored NS provide sufficient S. cypria yield and quality, while foliar Fe and Zn can be successfully implemented to improve the nutritional status of S. cypria, through appropriate P management.
Keywords: antioxidants; biofortification; foliar application; nutrient uptake; soilless cultivation